2019
DOI: 10.1111/mec.15017
|View full text |Cite
|
Sign up to set email alerts
|

How many came home? Evaluating ex situ conservation of green turtles in the Cayman Islands

Abstract: Ex situ management is an important conservation tool that allows the preservation of biological diversity outside natural habitats while supporting survival in the wild. Captive breeding followed by re‐introduction is a possible approach for endangered species conservation and preservation of genetic variability. The Cayman Turtle Centre Ltd was established in 1968 to market green turtle (Chelonia mydas) meat and other products and replenish wild populations, thought to be locally extirpated, through captive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 102 publications
(173 reference statements)
1
38
0
Order By: Relevance
“…However, the elevated genetic divergence could be due to sampling variance and smaller sample sizes (Table S3).
Figure 1Common Atlantic mtDNA haplotype proportions (CM-A01, CM-A03, CM-A05 and CM-A08; remaining haplotypes pooled under ‘Other’) in Lac Bay, Bonaire (BO; diamond) in 2006–2007 and 2015–2016 for <75.0 cm SCL juveniles (bottom-left insert ( A )) and <50.0 cm SCL juveniles (bottom-left insert ( B )) and in north-western (NW; triangles), south-western (SW; square), eastern (EA; circles) Caribbean and southern Atlantic (SA; crosses) green turtle rookeries: Aves Island, Venezuela (AV) 47,70 ; Buck Island, St. Croix, US Virgin Islands (BI) 47 ; Cayman Islands (CI) 74 ; Cuba (CU) 71 ; Tortuguero, Costa Rica (CR) 40,70 ; Central Eastern Florida, USA (EF) 72 ; French Guiana (FG) 73 ; Guadeloupe (GU) 73 , Quintana Roo, Mexico (MX) 70 ; South Florida, USA (SF) 72 ; Suriname (SU) 47,70,73 ; Rocas Atoll, Brazil (RA) 70,76 ; Fernando de Noronha, Brazil (FN) 76 ; Trindade Island, Brazil (TI) 76 ; Ascension Island, UK (AI) 70,75,79 ; Poilão, Guinea Bissau (GB) 70,75,77 ; São Tomé and Príncipe (ST) 75 ; Bioko Island, Equatorial Guinea (BIO) 75 .
…”
Section: Resultsmentioning
confidence: 99%
“…However, the elevated genetic divergence could be due to sampling variance and smaller sample sizes (Table S3).
Figure 1Common Atlantic mtDNA haplotype proportions (CM-A01, CM-A03, CM-A05 and CM-A08; remaining haplotypes pooled under ‘Other’) in Lac Bay, Bonaire (BO; diamond) in 2006–2007 and 2015–2016 for <75.0 cm SCL juveniles (bottom-left insert ( A )) and <50.0 cm SCL juveniles (bottom-left insert ( B )) and in north-western (NW; triangles), south-western (SW; square), eastern (EA; circles) Caribbean and southern Atlantic (SA; crosses) green turtle rookeries: Aves Island, Venezuela (AV) 47,70 ; Buck Island, St. Croix, US Virgin Islands (BI) 47 ; Cayman Islands (CI) 74 ; Cuba (CU) 71 ; Tortuguero, Costa Rica (CR) 40,70 ; Central Eastern Florida, USA (EF) 72 ; French Guiana (FG) 73 ; Guadeloupe (GU) 73 , Quintana Roo, Mexico (MX) 70 ; South Florida, USA (SF) 72 ; Suriname (SU) 47,70,73 ; Rocas Atoll, Brazil (RA) 70,76 ; Fernando de Noronha, Brazil (FN) 76 ; Trindade Island, Brazil (TI) 76 ; Ascension Island, UK (AI) 70,75,79 ; Poilão, Guinea Bissau (GB) 70,75,77 ; São Tomé and Príncipe (ST) 75 ; Bioko Island, Equatorial Guinea (BIO) 75 .
…”
Section: Resultsmentioning
confidence: 99%
“…Identifying genealogical relationships (i.e. kinship) among individuals has been instrumental in understanding important ecological questions of wild populations (Avise, 2004), such as mating systems (Griffith, Owens & Thurman, 2002; Vigilant et al ., 2015), dispersal (Arora et al ., 2012; Feldheim et al ., 2014; Salles et al ., 2016; Warner, Willis & van Oppen, 2016; Baetscher et al ., 2019), heritability (Dubuc et al ., 2014) and links to captive breeding and reintroduction programs (Barbanti et al ., 2019). Aside from observing parent–offspring interactions, kin relationships are typically unknown in wild populations but can be estimated by calculating the proportion of shared genetic material (identity by descent) between individuals (Blouin, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While nesting numbers have increased dramatically for these two species, it is important to consider this modern-day population increase in the context of historical levels of abundance in the 1600s, when the nesting turtle population in the Cayman Islands was estimated to be more than 2.5 million (Jackson, 1997). Today, the green turtle nesting population has been estimated at around 100-150 females (Barbanti et al, 2019) and nesting data suggests there are even fewer loggerheads turtles. Additionally, these populations are still experiencing several anthropogenic threats including illegal take of adult turtles and the impact of artificial lighting causing hatchling mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Through documentation of permanent marks known as "living tags, " the first farm-released green turtles were recorded nesting on Grand Cayman beaches in 2002, at an age of 15 years (1 individual) and 17 years (2 individuals) (Bell et al, 2005). A genetic study determined that 90% of wild nesting green turtles (n = 57) in Grand Cayman in 2013/2014 were related as either offspring or full or half-siblings to the turtle farm individuals (Barbanti et al, 2019) and our study showed that the majority of green turtle nesting occurs in close proximity to the Cayman Turtle Farm breeding location. Therefore, the increase in nest numbers detected in the early years of nest monitoring may have been driven by the turtles released from the Cayman Turtle Farm in the 1980s reaching maturity after more than two decades in the wild.…”
Section: Green Turtle Population Trendmentioning
confidence: 99%
See 1 more Smart Citation